The antifungal activity of essential oils from some plants in Vietnam against the pathogenic fungi Candida albicans and Aspergillus fumigatus - Vu Xuan Tao; Tran Bao Tram; Nguyen Thi Hien; Thai Hanh Dung; Tran Van Tuan (Vietnam Journal of Science, Technology and Engineering, 2022)
Vietnam possesses an abundant and highly diverse resource of plants. Therefore, the search and evaluation of bioactive compounds extracted from these plants are a potential research direction to support developing products that improve human health. The purpose of this study is to assess the antifungal activity of some essential oils produced by materials harvested in Vietnam such as King orange peel (Citrus sinensis), lemongrass (Cymbopogon flexuosus), peppermint (Mentha arvensis), and betel leaf (Piper betle). The antifungal effect of these essential oils was determined by the Kirby-Bauer disc diffusion technique. In addition, the antifungal properties of the essential oils were also assessed through their effects on the reproduction of C. albicans and the spore germination, mycelium elongation, and sporulation of A. fumigatus. The results demonstrated that all peppermint, lemongrass, and betel leaf essential oils showed antifungal activity against C. albicans and A. fumigatus. Especially, betel leaf essential oil could perform antifungal activity at a low dilution concentration of 10% and could also inhibit the reproduction of C. albicans and the spore germination, mycelium elongation, and sporulation of A. fumigatus. Meanwhile, orange peel essential oil did not exhibit any antifungal properties.